(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
HR analytics is being adopted by organizations and its importance has steadily increased to become more of a necessity. Since it is an emerging topic, this paper aims to present an overview of HR analytics’ content, scope, significance, opportunities and challenges in its applications. The methodology adopted was review of literature from 144 articles including 62 peer-reviewed ones selected from online search of three large databases with the terms ‘human resource/ workforce/ people/ talent analytics’, ‘human capital analytics and metrics’ and ‘predictive human resource analytics’. The study finds that HR analytics, as a concept, is still a developing one with further strengthening required on its several aspects. Analytics cannot replace HR but can definitely assist HR professionals in discharging their roles in an improved manner. The primary objective of HR analytics is to increase organizational effectiveness by way of better data-based managerial decisions. However, evidence about usage of HR analytics is limited. A universally acceptable definition for it is a potential area for research. The factors responsible for its adoption in general as well as in different research settings also need to be studied.